ANALISIS PENAWARAN UBI KAYU DI KABUPATEN WONOGIRI - Sundari, Mei Tri (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2006)
This research aim to study factors influencing the amount of cassava supply and also its elasticity effect of change of variable influencing it. Basic method used in this research is descriptive method. Research area taken by purposive that Sub-Province Wonogiri as biggest cassava producer area in Central Java. Type data in this research is obtained secondary data from releated institution. The analysis in this research is doubled linear regression analysis at offer function